2003
DOI: 10.1111/j.1469-8137.2004.00978.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution ecology of pollen tubes: fine‐grained, labile spatial mosaics in southern Spanish Lamiaceae

Abstract: Summary• Patterns of intraspecific variation in the number of pollen tubes per style in naturally pollinated plants are poorly known, yet that information is essential for assessing the frequency of occurrence and evolutionary implications of microgametophyte competition in the wild.• This paper analyses intraspecific variation in the number of pollen tubes per style for six species of southern Spanish insect-pollinated Lamiaceae ( Ballota hirsuta , Lavandula latifolia , Marrubium supinum , Phlomis lychnitis ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 47 publications
4
44
0
Order By: Relevance
“…Although aspects of the pollination process can, in some cases, influence variation in seed or fruit size (Waser 1978;Biere 1991;Dogterom et al 2000;Herrera 2004), results of our studies indicate that, rather than pollen load and donor diversity, intra-and interplant effects are the dominant source of variation in seed and fruit mass of senita. In the pollen supplementation experiment, 94% of variation in seed and fruit mass was explained by intra-and interplant effects (table 3).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Although aspects of the pollination process can, in some cases, influence variation in seed or fruit size (Waser 1978;Biere 1991;Dogterom et al 2000;Herrera 2004), results of our studies indicate that, rather than pollen load and donor diversity, intra-and interplant effects are the dominant source of variation in seed and fruit mass of senita. In the pollen supplementation experiment, 94% of variation in seed and fruit mass was explained by intra-and interplant effects (table 3).…”
Section: Discussionmentioning
confidence: 55%
“…Alternatively, any effect of pollen load on variation in seed and fruit size may be mediated by stigma clogging or pollen tube competition (Waser 1978;Herrera 2004). Though not directly examined, such factors may be important in senita, as their stigmas receive thousands more pollen grains than there are ovules (Holland and Chamberlain 2007).…”
Section: Discussionmentioning
confidence: 97%
“…For 13 animal-pollinated species, 50.4% to 100% of this variation was attributed to variation among flowers within individuals, whereas the remaining variation occurred among individuals (Herrera 2004(Herrera , 2009). In contrast, for wind-pollinated plants, amongplant variation likely plays a more dominant role than within-plant variation (Friedman and Barrett 2011).…”
Section: Discussionmentioning
confidence: 97%
“…For monocarpic species, which our model addresses most directly, Knight et al (2006) found that pollen supplementation of all flowers increased seed production, on average, by 13%. According to our model, this response would occur if 60% of the variation in pollen receipt occurs within plants, an estimate consistent with several naturally pollinated plant populations (Herrera 2002(Herrera , 2004(Herrera , 2009.…”
Section: Pollen Attractionmentioning
confidence: 97%
See 1 more Smart Citation